Elaboração e fundição de precisão - Chinaglia, Clever Ricardo [UNESP]; Filho, André Itman; Kiminami, Claudio Shyinti; Bolfarini, Claudemiro; Orlandi, Sérgia (My University, 1996)
This paper describes the methodology of an investment casting Al-Li-Cu-Mg alloy preparation. A zirconite based shell mold was used casting 12 tension test geometric samples. This alloy has been prepared from an Al-6,9%Li master alloy and cadding commercial purity magnesium, copper and aluminium. An argon atmosphere induction furnace was used and a high purity argon degaseification system. The shell mold was warmed up in a resistive furnace placed inside the induction furnace chamber. The mold temperature and its cooling rate, after shed, have been registered by a termocouple inserted in the mold wall. The samples have been evaluated under optical microscopy image analysis software, scanning electron microscopy, chemical analysis, densities measurements and tension tests. The methodology used in investment casting of this alloy has shown to be adequate, providing good quality samples with low porosity and inclusions levels, good chemical homogeneity and typical as cast microstructure.